DALSZY CIĄG DYSKUSJI KONSTYTUCYJNYCH - Winczorek, Piotr (Wydział Prawa i Administracji UAM, 2011)
W artykule omówiono i skomentowano propozycje zmiany Konstytucji RP z 1997 r., które zawarte są w projektach przedstawionych Sejmowi przez posłów: Prawa i Sprawiedliwości (w tym także projekt nowelizacji ustawy o Trybunale Konstytucyjnym), Platformy Obywatelskiej, oraz w projekcie wniesionym z inicjatywy Prezydenta RP. Nad tymi projektami dyskutuje od końca 2010 r. sejmowa Komisja Nadzwyczajna. Główne propozycje zmian konstytucyjnych koncentrują się wokół następujących kwestii: (a) zmniejszenia składu personalnego Sejmu i Senatu oraz ograniczeniu zakresu formalnego immunitetu parlamentarnego, (b) zmian w położeniu ustrojowym Prezydenta RP względem Sejmu i Rady Ministrów, (c) dekonstytucjonalizacji niektórych instytucji ustrojowych (Krajowa Rada Radiofonii i Telewizji, Rada Bezpieczeństwa Narodowego), (d) konstytucjonalizacji prokuratury i Krajowej Rad Prokuratorów, (e) zmiany położenia ustrojowego Narodowego Banku Polskiego i zniesienia Rady Polityki Pieniężnej w związku z planem przystąpienia Polski do strefy euro, (f) wprowadzenia pełniejszych regulacji dotyczących udziału Polski w Unii Europejskiej. Proponowane zmiany są niekiedy konieczne, ale są też takie, których należałoby − zdaniem autora artykułu − poniechać. Nie prowadzą one jednak do odejścia od ukształtowanego przez Konstytucję z 1997 r. porządku ustrojowego, ale jedynie do jego częściowej reformy.

The paper comments on the draft amendments to the Constitution of the Republic of Poland of 1997 (including a proposal of an amendment to the Law on the Constitutional Tribunal) contained in the proposals put forward by deputies of the Law and Justice and the Civic Platform parties, and those initiated by the President of Poland. Those draft laws have been discussed by the Sejm Extraordinary Committee since the end of 2010. The main proposals of constitutional amendments are focused on the following issues: (a) reduction in the staff of the Sejm and Senate and limitation of the formal scope of parliamentary immunity; (b) change in the position of President vis-a-vis the Sejm and the Council of Ministers in the adopted political regime; (c) de-constitutionalisation of certain national institutions (the National Radio and Television Committee, the National Safety Council); (d) constitutionalisation of the Public Prosecutor’s office and the National Council of Prosecutors; (e) change in the position of the National Bank of Poland in the adopted political regime, and liquidation of the Monetary Policy Council in connection of Poland’s anticipated access to the euro area; (f) implementation of more comprehensive regulations governing Poland’s membership in the European Union. Some of the proposed amendments are necessary indeed, but there are some which, in the author’s opinion, should be abandoned, as they are not going to result in a departure from the political regime shaped and adopted in the Constitution in 1997, but merely in its partial modification.
CONTINUATION OF THE DISCUSSION ON THE CONSTITUTION
Keywords: Konstytucja RP; The Constitution of the Republic of Poland; Projekty zmian; Draft amendments